ダイ 38 ジ ナンキョク チイキ カンソクタイ ドーム フジ カンソク キョテン エットウ ホウコク 1997-1998 - 金戸, 進; カネト, ススム; 山内, 恭; ヤマノウチ, タカシ; Kaneto, Susumu; Yamanouchi, Takashi (1999)
P(論文) 第38次南極地域観測隊ドームふじ観測拠点越冬隊9名は, 1997年1月25日から1998年1月24日までの1年間, ドームふじ観測拠点での3年目, 最終年の越冬観測を実施した。今次隊では, 気水圏系プロジェクト研究観測の「氷床変動システム研究観測」と「南極大気・物質循環観測」を主に実施した。前者では, 36次隊から続けられた氷床深層掘削が中心課題として計画されていたが, 前次隊末のドリルスタック以来, 液封液の補充を続けたがドリルを回収できず, 深層掘削の再開には至らなかった。しかし, 前年までに掘削された氷床コアの現場処理・解析を続け, 多くのコア試料を持ち帰った他, 雪氷観測, 浅層掘削, 内陸旅行観測を行った。後者では, 新たな観測として, ライダーによる極域成層圏雲の観測やGPSゾンデによる高層観測, 大気循環場の観測等を精力的に実施し, 初めて内陸での極成層圏雲の通年の盛衰を捉えたり大気循環場のブロッキング高気圧に伴う熱や水蒸気の流入を捉えるといった成果を上げることができた。これら観測を支える設営面では, 水作りのための雪取りや, 燃料ドラムの搬入, 低温下での車両の立ち上げに苦労した。燃料事情は厳しかったが, 昭和基地からの補給を行ったことで内陸調査旅行が可能となった。越冬最後に, 基地の閉鎖作業を行い, 基地を後にした。 The wintering party of the 38th Japanese Antarctic Research Expedition (JARE) at Dome Fuji Station, consisting of 9 personnel, carried out observation programs from January 25,1997 to January 24,1998,as the third and last year of the wintering. Project-oriented programs of meteorology and glaciaology, named "Change in Mass Balance and Dynamics of the Ice Sheet" and "Atmospheric Circulation and Material Cycle in the Antarctic" were mainly conducted. In the former project, deep ice core drilling had been planned to be continued; however, due to the stuck of drill during JARE-37,drilling could not be continued, and only analyses of ice cores drilled beforehand were carried out. Also, other glaciological observations, shallow core drilling and traverse observations were carried out. In the latter project, new observations of Polar Stratospheric Clouds (PSCs) using lidar and balloons, and aerological observation using GPS sondes and radiation measurements, were extensively made. The observations revealed the growth and decay of PSCs throughout the year and abrupt change of heat and moisture transport associated with wintertime blocking formation. The logistics, including digging snow for the water supply, carrying fuel drums into the station buildings from the depot and setup of vehicles during the severe cold winter were hard work. Supply of fuel from Syowa Station conducted during the austral spring made two traverse observations possible. ...